Дослідження антиадгезивних властивостей поверхнево-активних речовин Acinetobacter calcoaceticus ІМВ В-7241 - Скочко, А. Б.; Конон, Анастасія Дмитрівна; Пирог, Тетяна Павлівна (My University, 2012)
Препарати поверхнево-активних речовин (ПАР) Acinetobacter calcoaceticus ІМВ В-7241 (0,28 мг/мл) зменшували кількість прикріплених клітин Bacillus subtilis БТ-2 різного фізіологічного стану на кафелі на 38,7–45,8 % і лінолеумі на 79,1–85,8 %, Escherichia coli ІЕМ-1 – на сталі, пластику і кафелі на 41, 15 і 14 % відповідно. Такі препарати можуть бути використані як антиадгезивні компоненти дезінфікуючих засобів. It was established that drugs of surface-active substances (SAS) of Acinetobacter calcoaceticus ІМВ В-7241 in concentration 0,28 mg/ml reduced the number of attached cells of twenty-four-hour Bacillus subtilis BT-2 culture on ceramic tile per 41,3 % and linoleum per 82,4 %, Escherichia coli IEM-1 – on steel, plastic and ceramic tile per 41, 15 and 14 % respectively. It was shown that anti-adhesion activity of A. calcoaceticus ІМВ В-7241 SAS drugs caused a decrease in the number of attached cells of B. subtilis BT-2 depending on their physiological state, and effectively act on the spore culture (14.2% of attached cells on linoleum, 54.2% - on ceramic tile). Regardless of the physiological state of cells of B. subtilis BT-2 under the influence of surfactant drugs observed stimulation of adhesion to plastic, and E. coli IEM-1 - on linoleum. The results can be used for the development of disinfectants, in which the antiadhesive components may be the SAS of A. calcoaceticus IMB B-7241.
Keywords: Acinetobacter calcoaceticus; disinfectants; surfactants; поверхнево-активні речовини; дезінфікуючі засоби; кафедра біотехнології і мікробіології